Maximum energy product of exchange-coupled Sm(FeCo)12/α-Fe nanocomposite particle - Ryusei Uda; Kunihiro Koike; Nobuyuki Inaba; Hiroaki Kato; Masaru Itakura; Susumu Okubo; Hitoshi Ohta; Hiroki Tsuchiura (AIP Advances, 2023)
The effects of the coating surface orientation of the α-Fe soft magnetic layer on the Sm(Fe0.8Co0.2)12 hard magnetic phase and the volume fraction of α-Fe, VFe, on the maximum energy product, (BH)max of exchange-coupled Sm(Fe0.8Co0.2)12/α-Fe nanocomposite magnet particles were micromagnetics OOMMF package was systematically investigated. The (BH)max of the reference model, Sm(Fe0.8Co0.2)12 particles without Fe layer, was 630 kJ/m3. In contrast, in the nanocomposite magnet particle model with soft magnetic layers on both sides of the hard magnetic phase, (BH)max reached a maximum value of 657 kJ/m3 at VFe = 12% (Fe layer thickness, tFe = 2 nm). In the model with α-Fe coating on the top and bottom surfaces of the hard magnetic phase, (BH)max = 636 kJ/m3 at VFe = 4% (tFe = 2 nm). Furthermore, the coating of the soft magnetic phase on both sides of the hard phase particles reduces the magnitude of the demagnetizing field, Hd of the nanocomposite magnet particles, indicating that the side coating of the soft magnetic phase is effective in increasing (BH)max. These findings allow for a greater degree of freedom in the design of nanocomposite magnets by adjusting not only the VFe volume fraction of the hard/soft phases but also their arrangement.